Vidian Canal as a Transcranial Landmark: Anatomy, Technique, and Illustrative Cases - Zhao, Xiaochun; McKenzie, Daniel M.; Pelargos, Panayiotis E.; Palejwala, Ali H.; Dunn, Ian F. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The vidian nerve can be accessed in transcranial approaches in carefully selected patients to ensure its preservation and to serve as a landmark for sphenoid sinus entry. This report is to review a technique, evaluate it in laboratory settings, and present two illustrative cases.Design The study involves cadaveric dissection and illustrative cases.Setting The study conducted in a cadaveric dissection laboratory.Participants The object of the study is one cadaveric head and two illustrative clinical cases.Main Outcome Measures Two cases using this approach were illustrated, and a cadaver dissection was performed in a step-by-step fashion.Results: The vidian canal can be accessed by drilling the anterolateral triangle. Two illustrated cases were presented; in one, the vidian nerve was used as part of a corridor to access the sphenoid sinus for tumor delivery, and in the other, the technique was used to find and preserve the vidian nerve during transcranial resection.Conclusion Careful identification of the vidian canal in transcranial surgery is a beneficial technique in carefully selected cases which allows identification of the nerve both for its preservation in selected cases and to create the vidian–maxillary corridor for tumor resection. Knowing the anatomy and pneumatization variants is important in the surgical approach.
Keywords: vidian canal; meningioma; surgical approach; sphenoid sinus